KASUS "KUMPUL" SEBELUM KAWIN: TREND DAN KARAKTERISTIK INDIVIDU* - Sri Handayani Hanum (Populasi, 1996)
Basing on the age groups like, the last age, the first age group, and the marriage age, the proportion of the youth who get involved in premarital sexual relationship is evidently increasing from year to year. This has led to the emergence of various problems connected with unprotected sexuality and reproductive health of the youth. Up to 76.1 percent cases of premarital sexual activities were first carried out between age limits 21-71 years. Most of them involved students of high school and tertiary institutions. There is a tendency that the higher the level of education, the higher will be the degree of permissiveness towards premarital sexual relationship. Most of the new marriages involve pregnant cases of between 3-6 months. The proportion of premarital sex cases is higher in the urban areas compared to the rural areas.